2022
DOI: 10.7759/cureus.30735
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Success Rates of Post and Core Treated Anterior and Posterior Teeth Using Cast Metal Posts

Abstract: Background: Post and core restorations are performed (generally after treating the root canals of the tooth) when the majority of the tooth structure has been rendered ineffective to support itself/the crown of the tooth. In this clinical study, we aim to compare the difference between post and core treatment of anterior and posterior teeth and their success/failure rates.Objective: Our investigation aimed to compare the clinical survival rates of custom-fabricated cast metal post-and-cores in cases of anterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…Another study evaluated the success rates of post and core-treated anterior and posterior teeth using cast metal posts. The study found that the success rate of post and core-treated anterior teeth was higher than that of posterior teeth [ 20 ].…”
Section: Reviewmentioning
confidence: 99%
“…Another study evaluated the success rates of post and core-treated anterior and posterior teeth using cast metal posts. The study found that the success rate of post and core-treated anterior teeth was higher than that of posterior teeth [ 20 ].…”
Section: Reviewmentioning
confidence: 99%